Analisis Faktor-Faktor yang Mempengaruhi Pengukuran Pengungkapan Corporate Social Responsibility (CSR) Perbankan Syariah Berdasarkan Indeks Islamic Social Reporting (ISR) - Astuti, Susi (AKMENIKA, 2019)
The Corporate Social Responsibility (CSR) program is an investment for companies for the growth and sustainability of the company and is no longer seen as a cost center but as a means to become a profit center.The implementation of CSR in banking industry has the goal of making CSR as one of the companies to regulate their business not only for the benefit of shareholders but for other stakeholders. In addition, Corporate Social Responsibility (CSR) is also a challenge to maintain the company's reputation in the community.The issue of Corporate Social Responsibility (CSR) sticking out along with the development of a banking sector related to the need for disclosure of social responsibility in Islamic banking today, is widely discussed about the Islamic Social Reporting Index (ISR index). The ISR index contains compilation of standard items of CSR set by AAOIFI which were further developed by researchers regarding CSR items that should be disclosed by an Islamic entity. The Islamic Social Reporting (ISR) index is believed to be the initial benchmark in terms of disclosure standards for Corporate Social Responsibility (CSR) that are in accordance with the Islamic perspective. This research was conducted on Islamic banks in the Middle East region whose annual reports were announced through banking sites using a sample of Islamic bank annual reports published during the period 2015-2017.